2010
DOI: 10.1111/j.1556-4029.2010.01574.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Escalation and Problematic Approaches Toward Public Figures*

Abstract: Detailed comparison of factors associated with abnormal approach to the prominent and with escalation from communication to approach has not hitherto been undertaken. This partially reflects the failure of individual studies to adopt compatible terminologies. This study involves a careful dissection of six public figure studies, three involving U.S. politicians, two Hollywood celebrities, and one the British Royal Family. Common findings were unearthed across six headings. Approachers were significantly more l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(54 citation statements)
references
References 27 publications
(68 reference statements)
6
46
2
Order By: Relevance
“…They participate in social media, and their movements are easy to follow for those interested. Our survey found the same pattern as corresponding international studies show that the prevalence among MP is significantly higher than in the general population sample (James et al, 2007(James et al, , 2009Meloy et al, 2011). On one hand, politicians want contact with and feedback from voters, party members, and supporters and engaged laypersons.…”
Section: The Role and Risks Of Mpssupporting
confidence: 85%
“…They participate in social media, and their movements are easy to follow for those interested. Our survey found the same pattern as corresponding international studies show that the prevalence among MP is significantly higher than in the general population sample (James et al, 2007(James et al, , 2009Meloy et al, 2011). On one hand, politicians want contact with and feedback from voters, party members, and supporters and engaged laypersons.…”
Section: The Role and Risks Of Mpssupporting
confidence: 85%
“…Only a handful of studies on abnormal communications and approaches to prominent people have been carried out to-date and no compatible terminologies have emerged [2]. Yet, these studies have demonstrated that the occurrence of problematic approaches can be meaningfully related to quantifiable behavioral factors observed in abnormal communications and therefore offer a serviceable basis on which to develop a PPI approach.…”
Section: Executive Summarymentioning
confidence: 99%
“…As reported in [2], six studies have been carried out to date on abnormal communication and approach to prominent people: one on the British royal family [18], two on Hollywood celebrities [19,20], and three on the U.S. Congress [21,22,23]. The studies relate the occurrence of problematic approaches to factors such as mental illness, threatening or antagonistic communication, requests for help, multiple means of communication, and multiple contacts and targets.…”
Section: Existing Work On Abnormal Communications and Approachesmentioning
confidence: 99%
See 2 more Smart Citations